Gene Cloning of Xylanase Glycoside Hydrolase Family 11 from Bacillus halodurans CM1 in Escherichia coli DH5Î± - Muhamad Taufiqul Naufal; Agustin Krisna Wardani; IS HELIANTI (Indonesian Society for microbiology, 2019)
Xylanase is an enzyme that can break down xylan into xylose and xylooligosaccharide that is widely used in industry. Seeing the many applications of this enzyme, researchers conducted many studies on how to increase the productivity and effectiveness of the xylanase enzyme. One of the method that can be used to increase the xylanase enzyme production process is by using recombinant DNA technology such as cloning. Bacillus halodurans CM1 is a local alkalothermophilic bacterium that potential producer for xylanase and other industrial enzymes. This research was conducted to clone the GH11 xylanase coding gene from B. halodurans CM1 using pJET 1.2 / blunt plasmid as vector into Escherichia coli DH5Î± as cell host andÂ determine the nucleotide base sequence of the GH11 xylanase coding gene from B. halodurans CM1. The results showed the GH11 xylanase gene from B. halodurans CM1 was successfully cloned inÂ E. coli DH5Î± and based on the results of BLAST nucleotides had 99% similarities with that of endo-1,4-beta -xylanhydrolase (xyn11A) from B. halodurans C-125. Key words: Bacillus halodurans CM1, cloning, xylanase glycoside hydrolase family 11